Exploring change Management Practices and their impact on Organizational performance in the Indian IT Industry (Journal of Advances and Scholarly Researches in Allied Education, 2022)
The Indian IT industry is a dynamic and rapidly evolving sector that consistently encounters changes driven by technological advancements, market demands, and global economic trends. This study investigates the change management practices adopted by Indian IT organizations and evaluates their impact on organizational performance, employee satisfaction, and adaptability to market dynamics. A mixed-method approach, combining quantitative surveys and qualitative interviews, was employed to gather comprehensive insights. The findings reveal key strategies for successful change implementation and underline the importance of leadership, communication, and organizational culture in facilitating effective change.